Kinerja Perusahaan Daerah Air Minum Tirta Sinjai Bersatu dalam Pelayanan Air Bersih di Kabupaten Sinjai - Bahar, Asriyanti; Jamaluddin; Hermansyah (Indonesian Journal Publisher, 2024)
This study aims to process data and find out how the performance of the Tirta Sinjai Bersatu Regional Drinking Water Company in clean water services in Sinjai Regency and to find out the determinant factors of the performance of the Tirta Sinjai Bersatu Regional Drinking Water Company in clean water services in Sinjai Regency. This study uses a qualitative research methodology which is intended to provide an overall picture and description with guaranteed truth from the problem regarding the performance of the Tirta Sinjai Bersatu Regional Drinking Water Company in clean water services in Sinjai Regency. Data collection was carried out through observation, interview, and documentation methods. The data obtained were analyzed based on indicators determined by looking at the results of data collection from research informants, namely the Director of the Tirta Sinjai Bersatu Regional Drinking Water Company, Planning Staff, Head of Technical Division, Head of Customer Relations Division, and the community. That based on the results of the study regarding the performance of the Tirta Sinjai Bersatu Regional Drinking Water Company in clean water services in Sinjai Regency, it was concluded that it was not optimal because many customers still complained that the quality of the water distributed was salty water, cloudy, small water discharge, water mixed with mud and even dead water. And it is hoped that Perumda employees can be faster in providing services and overcoming obstacles that hinder the speed in serving customers.